Teste de respiração espontânea e avaliação da prontidão para extubação de recém-nascidos prematuros - Teixeira, Raphaela Farias (2020)
Spontaneous Breathing Trials (SBT) have been used to evaluate extubation readiness in Neonatal Intensive Care Units (NICU), aiming to improve successful extubation rates in preterm infants. However, studies about SBT in the neonatal population are still scarce, especially regarding the ideal duration of the test. Thus, this thesis had two objectives: I) to systematically review the literature about the accuracy of SBT as a predictor for extubation failure in preterm infants; and II) to evaluate the effects of a 5-minutes SBT and a 10-minutes SBT on successful extubation rates of very low birth weight (VLBW) infants compared to clinical judgment alone. The proposed methods involved a systematic review of the literature with meta-analysis and a double-blind randomized controlled clinical trial (RCT). The systematic review included six studies for qualitative and quantitative analysis, which performed the SBT with 3 or 5 minutes, using the endotracheal continuous positive airway pressure (ET-CPAP) mode and positive end-expiratory pressure (PEEP) equivalent to conventional ventilation. In these studies, the SBT showed a high pooled sensitivity (0.97; 95% CI 0.85-0.99), demonstrating that most of the infants that had a successful extubation were correctly identified by an approved test, but a low pooled specificity (0.40, 95% CI 0.24–0.58), with many false-positive cases, indicated inaccurate prediction of extubation failure. In the RCT, 88 VLBW infants from two NICU of Alagoas were randomized into three groups: control group, 5-minutes SBT group and 10-minutes SBT group. SBT was performed under ET-CPAP mode with PEEP 5 cmH2O, inspiratory flow 10 L/min and FiO2 of 30%. Test failure was determined if the infant had, at any time during the test: bradycardia lasting longer than 15 seconds, and/or dessaturation for more than 15 seconds; and/or signs of respiratory distress with a Silverman Andersen Respiratory Severity Score higher than 5. The primary outcome was successful extubation rate, defined as no need for reintubation within 7 days after extubation. The results showed no difference among the three groups in relation to the proportion of successful extubation rate (p = 0.644), bronchopulmonary dysplasia occurrence (p = 0.790) and hospital length stay (p = 0.175). In general, both the systematic review and the RCT performed here do not support the use of SBT in premature infants as the main criterion in the final decision to extubate it. The passed test may be accompanied by many false positives, not correctly identifying the infants that could fail in the extubation, and adding little value to the clinical judgment. On the other hand, a failed test may be more useful in clinical practice, since the probability of having a successful extubation in failed test infants has decreased. This may serve as a warning to the clinical team, stimulating the infant´s reevaluation, identifying the possible causes of this failure and judging the cost-benefit of postponing extubation.